2019
DOI: 10.3892/etm.2019.7550
|View full text |Cite
|
Sign up to set email alerts
|

Altered spontaneous brain activity patterns in patients with corneal ulcer using amplitude of low‑frequency fluctuation: An fMRI study

Abstract: The aim of the present study was to investigate the altered spontaneous brain activity in patients with corneal ulcer (CU) through the amplitude of low-frequency fluctuation (ALFF) technique and the association with their visual performance. A total of 40 patients with CU and 40 healthy controls (HCs) matched for sex, age and educational level were enrolled. Resting-state functional magnetic resonance imaging (rs-fMRI) was performed to examine the probands. Spontaneous cerebral activity variations were investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…in the present study, a notable decline in alFF values in the right iFG of type-2 diabetic patients with VH was observed, suggesting that VH may cause impairment of language function in this setting. The SFG is the marginal gyrus, accounting for approximately one-third of the human frontal lobe (39). using fMri experiments, Goldberg et al (40) demonstrated that the SFG was related to self-consciousness and coordinated with the movement of the sensory system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…in the present study, a notable decline in alFF values in the right iFG of type-2 diabetic patients with VH was observed, suggesting that VH may cause impairment of language function in this setting. The SFG is the marginal gyrus, accounting for approximately one-third of the human frontal lobe (39). using fMri experiments, Goldberg et al (40) demonstrated that the SFG was related to self-consciousness and coordinated with the movement of the sensory system.…”
Section: Discussionmentioning
confidence: 99%
“…The SFG is the marginal gyrus, accounting for approximately one-third of the human frontal lobe ( 39 ). Using fMRI experiments, Goldberg et al ( 40 ) demonstrated that the SFG was related to self-consciousness and coordinated with the movement of the sensory system.…”
Section: Discussionmentioning
confidence: 99%
“…Ogiso et al (2000) indicated that the precuneus also participates in motion image perception, and transmits motion signals to the supplementary motion area. Shi et al (2019) showed that the ALFF values of the right precuneus were decreased in PAAG patients;…”
Section: F I G U R Ementioning
confidence: 95%
“…The data were preprocessed with the Data Processing Assistant for resting‐state fMRI (rs‐fMRI; DPARSFA 4.0; http://rfmri.org/DPARSF), which was based on the rs‐fMRI Data Analysis Toolkit (REST; http://www.restfmri.net) and statistical parametric mapping (SPM; http://www.fil.ion.ucl.ac.uk/spm). This processing method has been described in detail previously (Shi et al., 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation